The use of sexually explicit material in sex therapy - Ratcliffe, G. Cole (Kansas State University, 2011)
Using data from a sample of 99 sex therapists in the United States who participated in an online survey, the use of sexually explicit material (SEM) in sex therapy is explored. Findings suggest that prevalence rates for the use of sexually explicit educational material and erotica in sex therapy were very high, 92.6% and 81.1% respectively; while the use of pornography was much lower at 29.5%. Younger therapists, and therapists with less experience, were more likely than older therapists and therapists with more experience to use SEM in sex therapy. Overall, sex therapists were generally comfortable with sexually explicit educational material and erotica but less comfortable with pornography. Younger therapists and/or female therapists were most comfortable with the use of pornography in sex therapy. The primary theoretical rationale reported by sex therapists for using SEM was education. Several therapists indicated that they would not recommend the use of SEM in sex therapy with clients who expressed opposition or discomfort, clients who exhibit compulsive sexual behaviors, and with clients who have a history of sexual trauma.
Keywords: Sexually explicit material; Sex therapy; Erotica; Pornography; Sexually explicit educational material; Psychology (0621)